Productive rationalities, technological changes and prioritizations for agrarian development in Puno - Claverías, Ricardo (1991)
In a time like the present, of urgent solutions to the food problem in Peru, thinking about agricultural development invites us to propose specific programs that promote the growth of agriculture and livestock. Based on ongoing research, this article proposes alternatives: a. The development of agricultural production technologies in peasant communities. b. The development of agricultural systems appropriate to the Altiplano. The goal in both cases should be to increase production and improve the standard of living of rural families.